PERENCANAAN STRATEGIS DENGAN ANALISIS SWOT DALAM MENINGKATKAN MUTU PENDIDIKAN DASAR DAN MENENGAH - Ahmad Agus Alim; Mugirah; Suwarno; Ngurah Ayu Nyoman Murniati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The era of globalization has greatly influenced various problems and challenges in the field of education in Indonesia. The quality of education management is very important in the process of improving the quality of education effectively and efficiently which can be seen from an education management process. Strategic planning is a necessity for educational institutions to prepare, carry out and implement it in all school activities to achieve goals in accordance with the vision and mission to improve the quality of education in both primary and secondary schools. Therefore, school principals must have appropriate strategies and analytical methods in making changes to the quality of education. SWOT analysis or method (strengths, weaknesses, opportunities and threats) is considered to be an approach in the context of strategic planning. The aim of this review is to analyze the impact of strategic planning with SWOT analysis on primary and secondary schools. This research is a literature study that looks for data sources in the form of information through an electronic database, namely Google Scholar. The research articles used are those that comply with previously determined criteria. The research results show that strategic planning with SWOT analysis has a positive impact on improving the quality of education in primary and secondary schools. Improving the quality or quality of education is directed at improving the quality of Indonesian people so that they have competitiveness in facing global challenges.